Regulating Fintech Based Peer-To-Peer Lending: A New Approach to SME Financing - Chitaka, Netsai (Department of Commercial Law, 2023)
Peer-to-peer (P2P) lending enables borrowers to obtain loans directly from lenders, without the need of a financial institution as an intermediary. The rising use of financial technology has increased the global adoption of P2P lending as an alternative to traditional unsecured lending. In contrast, hostile regulations (specifically within the National Credit Act) have created barriers preventing the scaling of local digital lending platforms. The goal of this research is to examine the role of P2P lending as potential funding solution for small and medium-sized enterprises (SMEs) struggling to access funding in an unbalanced credit market. This issue will be investigated with comparative reference to the varying regulatory positions that have been implemented in the United Kingdom, Belgium, China and Mauritius respectively. This study will advocate for the introduction of a regulatory sandbox in which P2P lending activities may be tested in a controlled environment under regulatory supervision. The results of this research aim to provide guidance for the implementation of a sustainable South African FinTech regulatory framework that would increase SMEs access to capital and manage risks in a way that does not stifle the development of this fast-growing innovative lending industry.